Short Sleep Duration and Screen-Based Activities: A Longitudinal Multilevel Analysis. Issue 4 (July 2018) - Alqaderi, Hend; Goodson, J. Max; Subramanian, S. V.; Tavares, Mary
Objective . The aim of this study was to identify lifestyle habits that contribute to night sleep reduction in the Kuwaiti population. Methods . Children were 10 to 12 years old and were approximately equally distributed among 138 elementary schools representing the 6 governorates of Kuwait. In the first phase of the study, data were collected from 8317 children. The same data were collected 2 years later from 6316 of the children from the first phase of the study. Calibrated examiners conducted sleep evaluation, lifestyle habits interviews, and body weight measurements. A multilevel random intercept and slope model was conducted to determine the effect of screen-based activities on the daily night sleep hours at 3 levels: within schools, among children, and over time. The primary dependent variable was the number of daily sleep hours. Independent variables assessed were lifestyle habits including screen-based activity variables including TV and video game use. Results . Screen-based activities were significant factors that reduced daily sleep hours (P < .05). There were statistically significant variations between schools and children over time. Conclusion. Longitudinal analysis of Kuwaiti children revealed that TV and video game use were major risk behaviors contributing to decreased sleep duration with strong clustering effect of the observations within schools across time.